2017
DOI: 10.1186/s12944-017-0455-0
|View full text |Cite|
|
Sign up to set email alerts
|

Hypercholesterolemia downregulates autophagy in the rat heart

Abstract: BackgroundWe have previously shown that efficiency of ischemic conditioning is diminished in hypercholesterolemia and that autophagy is necessary for cardioprotection. However, it is unknown whether isolated hypercholesterolemia disturbs autophagy or the mammalian target of rapamycin (mTOR) pathways. Therefore, we investigated whether isolated hypercholesterolemia modulates cardiac autophagy-related pathways or programmed cell death mechanisms such as apoptosis and necroptosis in rat heart.MethodsMale Wistar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…Hypercholesterolemia can inhibit autophagy in the heart of rats [ 23 ]. Finally, we examined the effect of simvastatin on autophagic flux in the jaw bone tissues of HCD-fed rats by quantitative RT-PCR and immunohistochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…Hypercholesterolemia can inhibit autophagy in the heart of rats [ 23 ]. Finally, we examined the effect of simvastatin on autophagic flux in the jaw bone tissues of HCD-fed rats by quantitative RT-PCR and immunohistochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…Changing systolic and diastolic blood pressure as well as contractile-induced dysfunction in rodents that are fed on HCD [8] have been reported. Studies showed that cardiac phagocytosis could prevent hypercholesterolemia in rats [9]. Increased cholesterol intake was found to impair the renal function and to provoke kidney damage in rodents [10].…”
Section: Introductionmentioning
confidence: 99%
“…Altered cardiac systolic and diastolic functions as well as contractile dysfunction were previously reported in rodents fed on HCD (3). In addition, basal cardiac autophagy was recently demonstrated to be suppresses by hypercholesterolemia in rats (4). Hypercholesterolemia was also reported in other studies to trigger lipids accumulation in liver, which negatively influence the hepatic functions (5,6).…”
Section: Introductionmentioning
confidence: 80%